Role of recombinant factor 7 in PPH: a new weapon in obstetrician’s armamentarium - Arun, Aage Priti; Verma, Savitri; Gandhi, Sudha; Jourwal, Aayush; Choudhary, Neeraj; Noorani, Zainab; Noorani, Zainab (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Post-partum hemorrhage (PPH) is a life-threatening obstetric complication and the leading cause of maternal death. It is currently managed mainly through surgical interventions with simultaneous transfusion of blood and blood-derived. However, in critical conditions the achievement of hemostasis and reversal of coagulopathy becomes more difficult. Here we are sharing an experience of 41 cases of severe PPH with different causes of PPH treated with new noninvasive advancement, recombinant factor 7 in PPH. Methods: This was a prospective observational study at Pannadhaya Rajkiya Mahila Chikitsalya Udaipur (Rajasthan) from May 2023 to December 2023. Here we are sharing an experience of 41 cases of severe PPH with different causes of PPH treated with new noninvasive advancement, recombinant factor 7 in PPH. Results: Out of 41 cases clinical response to rFVIIa (defined as bleeding decreased or stopped at 1 hour post administration) was seen in 26/41 (63%) patients. There was mortality of 5 patients. So, the total mortality rate was 12% in our study. Conclusions: Obstetric hemorrhage can progress rapidly and is strongly associated with the development of disseminated intravascular coagulation (DIC). Delayed correction of DIC is associated with a significant increase in morbidity and mortality. Rapid correction of coagulopathy with ongoing regular monitoring of coagulation status is often difficult to coordinate in the setting of acute life-threatening obstetric hemorrhage. Factor VII helps in haemostasis.